2022
DOI: 10.3390/rs14122754
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of Coniferous Forest Stock Volume Based on Backscatter and InSAR Coherence Factors of Sentinel-1 Hyper-Temporal Images and Spectral Variables of Landsat 8 OLI

Abstract: Forest stock volume (FSV) is a basic data source for estimating forest carbon sink. It is also a crucial parameter that reflects the quality of forest resources and forest management level. The use of remote sensing data combined with a support vector regression (SVR) algorithm has been widely used in FSV estimation. However, due to the complexity and spatial heterogeneity of the forest biological community, in the FSV high-value area with dense vegetation, the optical re-mote sensing variables tend to be satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…In this case, the R 2 obtained by SVR is significantly better than the other two models. This is because SVR can handle the strong nonlinear relationship between target parameters and satellite variables and achieve better estimation performance, even with limited sample data [96,97]. RF is a good choice when using horizontal structural indices or combining multiple structural indices as a variable.…”
Section: Analysis Of the Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the R 2 obtained by SVR is significantly better than the other two models. This is because SVR can handle the strong nonlinear relationship between target parameters and satellite variables and achieve better estimation performance, even with limited sample data [96,97]. RF is a good choice when using horizontal structural indices or combining multiple structural indices as a variable.…”
Section: Analysis Of the Model Resultsmentioning
confidence: 99%
“…Although the Pearson correlation coefficient selection variable method can simply and quickly select the characteristic variables that are linearly correlated with AGB, it is based on linear correlation and cannot fully and accurately describe the real relationship between biomass and remote sensing variables in complex forest environments. The RF feature selection method screens relatively key feature factors based on specific evaluation criteria, without considering the combination effect relationship between feature factors, which can lead to the selection of variables that do not better reflect the relationship with AGB [96]. LASSO uses constraint forms to identify smaller subsets of estimated variance and predictor variables with good variable selection and regularization capabilities [103].…”
Section: Analysis Of the Model Resultsmentioning
confidence: 99%
“…Recently, satellite-based SAR sensors with various bands (X, C, and L band) and various polarization (single, dual, and quad) SAR images have been widely applied in mapping Remote Sens. 2023, 15, 2253 2 of 18 forest parameters, such as TerraSAR-X, Rardarsat-2, ALSO-2 PALSAR, and Sentinel-1 [7,13]. Furthermore, previous results have shown that changes in wavelength and types of polarization modes resulted in differences in both analytical workflows and the achieved estimation performances [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…SAR data may be used alone for characterization of forest structure at the stand level (e.g., Gómez et al, 2021), but it may produce synergies with optical data (e.g., Li et al, 2022), and even be advantageous under persistently cloudy circumstances. Although backscatter intensity is more frequently employed, interferometric approaches provide further opportunities, by exploiting the phase difference and the scene coherence between various data acquisitions.…”
Section: Discussionmentioning
confidence: 99%
“…En las últimas décadas se han desarrollado una gran variedad de técnicas con multitud de aplicaciones en diversos campos (Tsokas et al, 2022), por lo que se clasifican los usos y aplicaciones de los datos SAR en tres categorías en función de su objetivo final: (i) mapeo y clasificación de terrenos: identifican y clasifican el tipo de superficie (Dostálová et al, 2018;Nikaein et al, 2021), el monitoreo forestal (Pulella et al, 2020a;Ygorra et al, 2021) y los derrames de petróleo (Dasari et al, 2022), por ejemplo; (ii) recuperación de parámetros: como la estimación de humedad (Barrett et al, 2009;Dorigo et al, 2017;Paloscia et al, 2013), el cálculo de la biomasa aérea (Cartus et al, 2022;Cartus y Santoro, 2019;Ghosh y Behera, 2021) o la estructura del dosel vegetal (Li et al, 2022;Pinto et al, 2013); y (iii) detección de objetos: para localizarlos e identificarlos en las imágenes, como el petróleo en el mar (Chaudhary y Kumar, 2020).…”
Section: Sensores Sarunclassified